2006
DOI: 10.1529/biophysj.105.068650
|View full text |Cite
|
Sign up to set email alerts
|

Formation Kinetics of Insulin-Based Amyloid Gels and the Effect of Added Metalloporphyrins

Abstract: The kinetics of insulin-based amyloid gel formation has been studied using extinction and fluorescence detection. The process is treated as autocatalytic, and the kinetic profiles are fit using a nonconventional analysis involving a time-dependent rate constant (factor): k(t) = k(o) + k(c)(k(c)t)(n). The dependence of the kinetic parameters on initial solution conditions of concentration, pH, and ionic strength has been investigated. A mechanism is proposed in which the rate-determining step involves the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…It was previously shown that anionic tetrakis(4‐sulfonatophenyl)porphine inhibits insulin fibrillization, while cationic tetrakis( N ‐methylpyridinium‐4‐yl)porphine has no significant effect on amyloids formation . Here, we observed the same effect for metal‐free tetraphenylporphyrins—inhibitory effect on insulin aggregation of amino‐substituted (cation‐forming) TPPN4 was essentially lower than that for carboxy‐substituted (anion‐forming) TNNC4.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It was previously shown that anionic tetrakis(4‐sulfonatophenyl)porphine inhibits insulin fibrillization, while cationic tetrakis( N ‐methylpyridinium‐4‐yl)porphine has no significant effect on amyloids formation . Here, we observed the same effect for metal‐free tetraphenylporphyrins—inhibitory effect on insulin aggregation of amino‐substituted (cation‐forming) TPPN4 was essentially lower than that for carboxy‐substituted (anion‐forming) TNNC4.…”
Section: Resultssupporting
confidence: 78%
“…Besides, the ability of porphyrin and hematin to inhibit tau fibril assembly was shown as well . The series of cationic tetrakis( N ‐methylpyridinium‐4‐yl)porphine and anionic tetrakis(4‐sulfonatophenyl)porphine complexes having a range of central metal atoms were studied for their effect on insulin aggregation; high inhibitory activity of anionic metalloporphyrins and their effect on structure of insulin aggregates were reported …”
Section: Introductionmentioning
confidence: 99%
“…For instance, H 2 PcS 4 suppresses the formation of ␣-synuclein amyloid, a pathological factor in Parkinson's disease (13). Tetrasulfonated porphyrins inhibit the aggregation of insulin (16), and hemin analogs delay fibril formation by the A/␤ peptide associated with Alzheimer's disease (7). These observations raise the possibility that cyclic tetrapyrroles have similar mechanisms of action in slowing the formation of a variety of pathological protein aggregates.…”
mentioning
confidence: 99%
“…For example, the influence of added metalloporphyrins on the rate and extent of gel formation of insulin was shown in Ref. [20]. Enhancement of fluorescence of poly(phenylene ethylene) substituted with anionic 3-sulfonatopropyloxy groups (PPESO 3 ) by bovine serum albumin was reported in [21], while fluorescence quenching of PPESO 3 by three cationic oxacarbocyanine dyes was demonstrated in [22] where the quenching efficiency was shown to be controlled by the stability of the polymer-dye association complex.…”
Section: Introductionmentioning
confidence: 99%